2015
DOI: 10.1016/j.tre.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain collaboration and incentives: Current trends and future directions

Abstract: This editorial piece discusses the current trends and future research directions in green supply chain collaboration and incentives. The discussion begins with evolution of green supply chain collaborations and few contributions made so far. The editorial piece introduces the special issue papers which address the green collaboration challenges and offers a general framework suggesting pathways for future research. The article ends with the open research questions in green supply chain collaborations and incen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(88 citation statements)
references
References 14 publications
1
86
0
1
Order By: Relevance
“…Ding et al [120] investigate the impact of government incentives on economic performance in the collaborative supply chain system. Gunasekaran et al [121] define a number of initiatives concerning the integration of green initiatives and cooperation between the supply chain partners. Lee et al [122] develop a survey to validate a model on the relationship among different parameters used to verify the performance of GSCM initiatives.…”
Section: Ta3 Impact Of Energy Efficiency and Environmental Sustainabmentioning
confidence: 99%
“…Ding et al [120] investigate the impact of government incentives on economic performance in the collaborative supply chain system. Gunasekaran et al [121] define a number of initiatives concerning the integration of green initiatives and cooperation between the supply chain partners. Lee et al [122] develop a survey to validate a model on the relationship among different parameters used to verify the performance of GSCM initiatives.…”
Section: Ta3 Impact Of Energy Efficiency and Environmental Sustainabmentioning
confidence: 99%
“…Thus, effective collaborative strategy is anticipated (e.g. performance enhancement in the form of better information quality, reduced costs, improved responsiveness) to enhance SC performance by enabling a decision-making process that echoes an extensive insight of the SC (Gunasekaran, Subramanian, and Rahman 2015).…”
Section: • Supply Chain Performance (Scp)mentioning
confidence: 99%
“…By analyzing the data, they found that external environmental factors including customer pressures, regulatory pressures, government supports, and environmental uncertainty were the most important in adopting green practices. Gunasekaran [11] discussed the current trends and future research directions in green supply chain collaboration and incentives. Sheu et al [12] presents an optimization-based model to deal with integrated logistics operational problems of green-supply chain management (G-SCM).…”
Section: Related Studiesmentioning
confidence: 99%